Entrepreneurship Education Mediation Model in Students' Entrepreneurial Intention: The Role of Risk Perception, Entrepreneurial Attitude, and Entrepreneurship Training - Sitti Hajerah Hasyim; Andika Isma; Agung Muliaman Anas (Pinisi Journal of Entrepreneurship Review, 2026)
Higher education institutions have a strategic role in encouraging entrepreneurial growth by strengthening entrepreneurial intention among students. Entrepreneurship education not only conveys concepts, but also shapes students' perspectives on risk, fosters entrepreneurial attitudes, and strengthens practical readiness through entrepreneurship training. This study aims to analyze the effects of risk perception, entrepreneurial attitude, and entrepreneurship training on students' entrepreneurial intention, with entrepreneurship education as a mediating variable. The study uses a descriptive-explanatory quantitative approach with a population of students from 8 study programs at the Faculty of Economics and Business, Universitas Negeri Makassar. The sample was determined using proportional random sampling, totaling 101 students. The analysis was conducted to test the direct and indirect (mediating) effects among variables in the research model. The results show that risk perception, entrepreneurial attitude, and entrepreneurship training affect entrepreneurial intention both directly and through entrepreneurship education as a mediator. These findings indicate that strengthening the quality of entrepreneurship education is key to optimizing the effects of attitudes, risk perception, and training on students' entrepreneurial intention. Practically, the results can serve as a reference for lecturers and study program managers in designing more applicable entrepreneurship learning that is integrated with training, strengthening managerial skills, marketing, and decision-making based on business evaluation. Future research is recommended to broaden the scope of variables and develop methodological designs so that understanding of the formation of entrepreneurial intention becomes more comprehensive.